Electrospinning of Ionic Supramolecular Azo Complexes. Issue 1 (February 2014) - Wang, Xiaoxiao; Zhang, Qian; Bazuin, C. Geraldine; Pellerin, Christian; Bulavin, Leonid; Guenet, Jean‐Michel
Summary Electrospinning was applied to DMF solution mixtures of poly(methyl methacrylate) (PMMA) and MO/PVP, which is an azo‐containing liquid crystalline complex between methyl orange (MO) and methylated poly(4‐vinyl pyridine) (PVP), to obtain composite light‐responsive fibers. The average diameter of the fibers, which ranged from 700 nm to 1.5 µm, increases with PMMA content. Differential scanning calorimetry, X‐ray diffraction and transmission electron microscopy show that they are microphase separated in the form of interspersed nanostrips of PMMA‐rich and MO/PVP(‐rich) phases. The MO/PVP(‐rich) phase is liquid crystalline (smectic A) as in the bulk, but with no orientation relative to the fiber axis. The birefringence of the fibers observed by polarized optical microscopy is attributed, at least in part, to form birefringence. This study is promising for the preparation of light‐responsive fibers based on easy‐to‐prepare polymer complexes.